Responsabilidade social do NUFACE/UFC e o alcance dos serviços prestados à comunidade - Moreira, Claudênia de Lima (2024)
In the context of constant changes and transformations that society has undergone over recent decades, the social role of public organizations has increasingly been demanded, especially that of the University, which has distinguished itself through its contribution to overcoming social barriers via extension activities— a fundamental link between education and society. In this sense, the actions proposed by Social Responsibility foster a discussion on the purpose of organizations within the community, potentially ensuring that it is part of a strategic plan aimed at generating sustainability and ethical values. Thus, the study will examine the social responsibility of the Facial Defects Core Project (NUFACE), an extension activity of the Faculty of Pharmacy, Dentistry, and Nursing (FFOE) at the Federal University of Ceará (UFC), which originated in mid-1996, observing social, environmental, control, and transparency criteria. It is noteworthy that the agenda for public policy evaluation is relatively recent in Brazil, emerging as a result of the State Reform with a neoliberal agenda, which focused on free market principles and privatizations with external demands, promoted by international organizations through the World Bank in exchange for funding (RODRIGUES, 2008; ROBERTIZON et al, 2012). Given this context, to achieve the research objectives, the methodology will employ the in-depth evaluation principles of Léa Rodrigues and the Content Analysis of Bardin (1977). Consequently, although the proposed policy is situated in a universe predominantly influenced by a positivist understanding, often directed by efficiency and quality parameters, the study aims to encompass the environment surrounding the extension activity and emphasize the social dimension of the project, from the perspective of the subjects, bridging theory and context (GUSSI et al, 2019). This does not disregard that the action is part of higher education and public service, which is strategically important for the social and economic development of the country.